1991
DOI: 10.1295/polymj.23.15
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between an Anionic Amphiphilic Sequential Polypeptide and Anionic Bilayer Membrane

Abstract: ABSTRACT:The interaction between an anionic amphiphilic sequential polypeptide and an anionic bilayer membrane composed of sodium dilaurylphosphate (DLPNa) was investigated and compared with hydrophobic polypeptide-DLPNa bilayer membrane and anionic polypeptide-DLPNa bilayer membrane interactions. A hydrophobic polypeptide, poly(y-methyl L-glutamate) (PMG, M,=4400), was incorporated into the DLPNa bilayer membrane due to their hydrophobic interaction. The incorporation of PMG, however, did not effectively incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We have already reported that several amphiphilic sequential polypeptides associate to form high-order micellar aggregates in aqueous solution4 and transmembrane bundles in bilayer membranes. 5,6 Here we demonstrate a photoinduced structural control of aggregates composed of photoresponsive amphiphilic sequential polypeptides, am aqueous solution containing 0.1 M KC1 at pH 6.9 (-• -), and a DPPC vesicle (-).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have already reported that several amphiphilic sequential polypeptides associate to form high-order micellar aggregates in aqueous solution4 and transmembrane bundles in bilayer membranes. 5,6 Here we demonstrate a photoinduced structural control of aggregates composed of photoresponsive amphiphilic sequential polypeptides, am aqueous solution containing 0.1 M KC1 at pH 6.9 (-• -), and a DPPC vesicle (-).…”
Section: Resultsmentioning
confidence: 95%
“…In a previous study, we reported a preparation of an amphiphilic sequential polypeptide by a monolayer reaction method4 and a bundle arrangement of the polypeptides in bilayer membranes. [5][6][7] The polypeptides formed an amphiphilic a-helix that is hydrophilic on one face (which consists of L-glutamic acid side chains) and hydrophobic on the opposite face (which comprises '/-methyl L-glutamate side chains). The amphiphilic a-helices were incorporated into the bilayer membrane to form the transmembrane bundle with a hydrophilic inner pore surrounded by hydrophilic Lglutamic acid side chains and a hydrophobic exterior, composed of hydrophobic /-methyl L-glutamate, in contact with the hydrocarbon region of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The polypeptides formed amphiphilic α-helices that are hydrophilic on one face (which consists of l -glutamic acid side chains) and hydrophobic on the opposite face (which comprised γ-methyl l -glutamate side chains). The amphiphilic α-helices were incorporated into a vesicular membrane and provided an ion permeable pore through the membrane. Furthermore, we prepared a photoresponsive amphiphilic sequential polypeptide composed of two amphiphilic α-helices joined by azobenzene (am.-MAzoM, Scheme ) . The am.-MAzoM was also incorporated into the vesicular membrane and formed ionic pores in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…The amphiphilic R-helices were incorporated into a vesicular membrane and provided an ion permeable pore through the membrane. [8][9][10] Furthermore, we prepared a photo-responsive amphiphilic sequential polypeptide composed of two amphiphilic R-helices joined by azobenzene (am.-MAzoM, Scheme 1). 11 The am.-MAzoM was also incorporated into the vesicular membrane and formed ionic pores in the dark.…”
Section: Introductionmentioning
confidence: 99%